Influence of EP additive on tool wear in drilling of compacted graphite iron - Alves,Salete Martins (2011)
Compacted Graphite Iron (CGI) is a good option for the manufacturing of engine blocks, because of the possibilities to decrease the wall thickness and to operate at higher pressures. However, due to its greater tensile strength and hardness compared with grey cast iron, the pearlitic CGI structure makes its machining more difficult. Thus, the aim of this paper is to investigate the improvements in CGI drilling achieved through the use of cutting fluids with EP additives. Experimental investigation of the influence of an EP additive on the drilling process was carried out using a CNC machine with 7.64 kW of power and maximum rotation of 5000 rpm. The cutting parameters were a cutting speed of 110 m/min, feed velocity of 350 mm/min and hole-depth of 20 mm. Three cutting fluids were analyzed, with and without EP additives. The results showed that the EP additive influenced the CGI drilling performance due to a layer comprised of sulphur (EP additive) and metal. Adhesion was avoided and the friction and wear behavior was improved.